Smart Absen Siswa dan Guru dengan Menggunakan Computer Vision pada Mafatih Islamic School Tebet - Dadang Iskandar Mulyana; Sopan Adrianto; Muhammad Rifqi Syatria; Muhammad Rival; Rodhi Shafia Zaidan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
An integrated technology-based attendance system was developed to address the inefficiencies of queuing and the dependency on manual input at Mafatih Islamic School. The proposed solution leverages a ResNet model within the dlib framework (Python) alongside a Laravel API for real-time face detection using a camera installed at the entrance. Data is temporarily stored in SQLite as an offline backup and later transmitted to the server in base64 format, accompanied by bounding box visualization as audit evidence.This system is capable of handling.